Evaluación de las condiciones de aplicación de los aditivos para cobre en medio ácido y alcalino con marca DR. Hesse en la industria marroquinera y eléctrica en el sector metálico a nivel laboratorio (2016)
This degree project aims to assess the conditions of application of additives HAG 90 (Carrier, Brigthener) with German brand Dr. Hesse in the electrodeposition of copper in alkaline médium for G y G engineering industry and additives Primus EX - 200 Brigthener, Primus and Primus Brigthener -520 EX EX - 520 Leveller for copper in acid medium in the Industrias Tiber. For this purpose samples of each of these companies were taken later they said samples taken to the laboratory and they made the respective analysis consistent with that described in the technical specifications (analytical marches, physical properties and performance in cell Hull), there is he failed to show that electrolytes did not meet the appropriate operations specifications or with the correct concentrations of additives, for this reason we proceeded to outline the processes and respective failures.